Prosecutorial activity through the prism of a systematic approach - Golovko, Irina (Известия высших учебных заведений. Поволжский регион: Общественные науки, 2023)
Background. The legislation on the Prosecutor’s office of the Soviet period and the modern Federal Law “On the Prosecutor’s Office of the Russian Federation” are united in defining the prosecutor's office as a system. However, consistency is manifested not only in the organization of the prosecutor’s office. In this regard, attention is drawn to scientific works and current practice of prosecutorial activity. Materials and methods. The solution of research tasks is provided by reference to legislation, selection and study of scientific papers, materials of judicial practice. This made it possible to identify the features of a systematic approach in the implementation of prosecutorial activities. Results. The system of legal means of the prosecutor is formed both on the basis of the prosecutor's tasks to be solved, and on the basis of the implementation of supervisory or non-supervisory activities. Ideas about the prosecutor’s inspection as a system are developed. Prosecutor’s inspection from the standpoint of a systematic approach can be considered as an element of the system of means of prosecutorial activity and as a system of verification actions. The elements of the system of conditions of the prosecutor's inspection – the reasons and grounds for the inspection are considered. Conclusions. A systematic approach makes it possible to ensure the completeness of the study of certain aspects of prosecutorial activity, as well as to develop ideas about the main categories. The conclusion is made about the prospects of a systematic approach in the study of prosecutorial activity and the improvement of relevant legislation.